2013
DOI: 10.1142/s1088424613500521
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and photophysical properties of a porphyrin-perinaphthothioindigo dye

Abstract: A new porphyrin-perinaphthothioindigo composite, where porphyrin and perinaphthothioindigo dye are connected though a triple bond, was synthesized. In UV-vis absorption spectra of the composite, absorption originating from the trans-isomer appeared at 655 nm. Upon photoirradiation at > 700 nm, the intensity of this absorption decreased with increase of absorption of the cis-isomer around at 530 nm. The HOMO-LUMO absorption of the cis-isomer is blue-shifted by 125 nm compared to that of trans-isomer due to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In 2007, we reported a photochromic porphyrin-perinaphthothioindigo conjugate having high 2PA efficiency [52][53][54]. As mentioned in the Introduction, we previously found that the ethynylene linking between porphyrins enhanced significantly the 2PA efficiency [20,21].…”
Section: Scheme 12mentioning
confidence: 92%
“…In 2007, we reported a photochromic porphyrin-perinaphthothioindigo conjugate having high 2PA efficiency [52][53][54]. As mentioned in the Introduction, we previously found that the ethynylene linking between porphyrins enhanced significantly the 2PA efficiency [20,21].…”
Section: Scheme 12mentioning
confidence: 92%